Bedhaya Sumreg Keraton Yogyakarta - Budi Astuti; Anna Retno Wuryastuti (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2012)
Penemuan jejak masa lalu atas keberadaan suatu bentuk budaya, merupakan suatu fenomena yang sangat bernilai. Hal ini dapat melengkapi upaya menelusuri jejak masa lalu dengan ditemukannya susunan materi gerak untuk visualisasi teks tarinya. Namun demikian tafsir kebudayaan atas penemuan jejak masa lalu tersebut tidak bisa meninggalkan faktor kesejarahannya. Dalam kajian teks bedhaya Sumreg ini diketahui susunan materi gerak Bedhaya Sumreg dan keterkaitan makna sumreg dengan pola lantai dan pola gendhing pengiringnya. Pola-pola gendhing yang ditampilkan secara struktural tetap menggunakan tata aturan baku yang sampai sekarang lazim disebut dengan lampah bedhayan. Bedaya yang dianggap pusaka ini diungkapkan tidak hanya materi tekstualnya saja tetapi juga mencakup materi kontekstualnya.Kata kunci: bedhaya Sumreg, tari Yogyakarta, tari pusaka.ABSTRACTBedhaya Sumreg of Yogyakarta Palace. The discovery of the past existence traces of a culture is trully a valuable phenomenon. This may complete the efforts to trace the past with the discovery of the structure of motion for the textvisualization of a dance. However, the interpretation of culture on the discovery of traces of the past cannot abandon the historical factor. The textual study of Bedhaya (traditional dance) Sumreg has identifi ed the motional structure of Bedhaya Sumreg and the linkage of Sumreg meaning with the fl oor pattern and gendhing (the accompanied music). Thepatterns of gendhing structurally shown remain applying predefi ned set of rules, commonly known as lampah bedhayan (rules in dancing). Bedhaya (traditional dance) is considered a heritage and is revealed not only its textual material but also the contextual one.Keywords: bedhaya Sumreg, Yogyakarta dance, dance heritage.